Maxim Law Fiqh And Its Application During The Covid-19 Pandemic - Abdul Hakim (NUSANTARA: Journal Of Law Studies, 2022)
Fiqh legal maxims is another name for qawaid fiqhiyyah. So the focus of this study is qawaid fiqhiyyah itself, with the main issues that will be asked and discussed about how to apply and apply during the Covid-19 pandemic. This research is a type of library research with data analysis techniques using content analysis. Primary data sources consist of several books and books that discuss and explain qawaid fiqhiyyah. In addition, the author also analyzes various fatwas, articles and opinions of scholars or figures regarding qawaid fiqhiyyah and their application during the Covid-19 pandemic. Based on the results of the sharp analysis that we have carried out, the legal maxims or qawaid fiqhiyyah have made a major contribution in determining the law of an event that occurred during the Covid-19 pandemic. This fact can be ascertained and found in various Islamic studies, both in the form of fatwas, articles and individual opinions. Some of the points of fiqh legal maxims that become the main focus and consideration in determining Islamic law are dar'u al-mafasid muqaddamun 'ala jalbi al-mashalih, al-dhararu yuzalu, al-masyaqqatu tajlibu al-taysir, al-dhararu tubiihu al-mahdzurat and ma ubiiha li al-dharurati yuqaddaru diqadriha. Thus, the presence of these legal maxims has made it easier for Islamic law experts in their application to decide and establish laws against cases faced by the world's Muslim community, especially in Indonesia during the Covid-19 pandemic.